How Do Nursing Students Perceive Care Towards the LGBTIQ+ Community? A Phenomenological Study on Sexual and Gender Diversity - Carlos Daniel Lemus Celin; Candy Laurine Suarez-Albor; Felice Curcio; Dhurata Ivziku; Olga Esther Hernandez Almanza; Mauro Giovanni Carta; Cesar Iván Avilés González (Nursing Reports)
Background/Objectives: Care-oriented perspectives in the LGBTIQ+ community are essential to ensure adequate and comprehensive health care. This population faces multiple barriers imposed by society, including discrimination in access to healthcare services. This research aims to analyse the perspective of nursing students in relation to the provision of care for people with sexual and gender diversity. Methods: A qualitative phenomenological research-action study was conducted. Data were collected using a semi-structured face-to-face interview consisting of 23 questions. The interviews were transcribed, read thoroughly and analysed. Results: Forty students were interviewed, and four main themes emerged: (1) personal perspective, (2) professional and disciplinary training, (3) nursing education and (4) health implications. The results show that students have mixed perspectives and attitudes towards LGBTQ+ populations, although they are interested in receiving more LGBTQ-focused training. Furthermore, respondents reported that the training received in the degree course and the preparation of lecturers in relation to caring for LGBTQ+ people are lacking. Finally, it emerged that inequalities in access to health services can still be observed and that there is a need for the development of manuals that are at the forefront of comprehensive health in this population. Conclusions: Based on the results, the implementation of Madeleine Leininger’s Sunrise model is suggested. Acceptance of sexual and gender diversity is essential to ensure the elimination of inequalities and make care a transformative process. Finally, education on these aspects needs to be implemented by including activities such as practical training scenarios, workshops and conferences to highlight the specific needs of the LGBTIQ+ population.